Influence of M23C6 dissolution on the kinetics of ferrite to austenite transformation in Fe-11Cr-0.06C stainless steel. (15th January 2019) - Miotti Bettanini, Alvise; Ding, Lipeng; Mithieux, Jean-Denis; Parrens, Coralie; Idrissi, Hosni; Schryvers, Dominique; Delannay, Laurent; Pardoen, Thomas; Jacques, Pascal J.
Abstract: The design of high-strength martensitic stainless steels requires an accurate control over the stability of undesired phases, like carbides and ferrite, which can hamper strength and ductility. Here, the ferrite to austenite transformation in Fe-11Cr-0.06C has been studied with a combined experimental-modelling approach. Experimental observations of the austenization process indicate that austenite growth proceeds in multiple steps, each one characterized by a different transformation rate. DICTRA based modelling reveals that the dissolution of the M23 C6 Cr-rich carbides leads to Cr partitioning between austenite and parent phases, which controls the rate of transformation through (i) a soft-impingement effect and (ii) consequent stabilization of the ferrite, which remains untransformed inside chromium-enriched-zones even after prolonged austenization stage. Slow heating rate and smaller initial particle sizes allow the design of ferrite-free microstructure. Graphical Abstract: Highlights: The microstructure design of stronger martensitic stainless steels hinges on austenization kinetics. Cr-rich carbides controls the transformation kinetics due to Cr partitioning and stabilization of ferrite. Coarse carbides and fast heating rates lead to a soft-impingement of the Cr diffusion fields ahead of austenite interface. Ferrite-free microstructures can be produced for slow heating rate or smaller initial carbides.